Clover Twig & The Incredible Flying Cottage - "Umansky, Kaye" (Bloomsbury Children's: London, 2008)
"Clover Twig stood at the garden gate, staring in at the witch's cottage - and the cottage stared right back. The windows were like black eyes - small, dark and hollow - and ivy dropped over them like hooded eyelids."
Keywords: English- Children's fantasy